2014
DOI: 10.1021/tx5002783
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Induced Overexpression of Inflammatory Cytokines Based on the Human Urothelial Cell Model in Vitro and Urinary Secretion of Individuals Chronically Exposed to Arsenic

Abstract: Chronic persistent inflammation could play an important role in the pathogenesis of some malignancies, and inflammation is a critical factor for bladder cancer development. In this study, we measured urine levels of transforming growth factor-α (TGF-α), tumor necrosis factor-α (TNF-α), and IL-8 in arsenic exposure workers and expressions of inflammatory cytokines in human urothelial cells in vivo and in vitro. We found the concentrations of IL-8, TNF-α, and TGF-α presented in urine were significantly elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Moreover, increased the secretion of inflammatory factors and IL-8, TNF-α, and TGF-α expression have also been observed to be induced by arsenic exposure [119]. It is well known that arsenic species in particular trivalent methylated arsenic intermediate metabolites have high binding affinity for the cysteine residues of proteins, however, arsenic has also been recognized for inhibiting the functioning of various transcriptional co regulators, proteins and enzymes [120123].…”
Section: Toxicities Of Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, increased the secretion of inflammatory factors and IL-8, TNF-α, and TGF-α expression have also been observed to be induced by arsenic exposure [119]. It is well known that arsenic species in particular trivalent methylated arsenic intermediate metabolites have high binding affinity for the cysteine residues of proteins, however, arsenic has also been recognized for inhibiting the functioning of various transcriptional co regulators, proteins and enzymes [120123].…”
Section: Toxicities Of Arsenicmentioning
confidence: 99%
“…Notably , regarding the trivalent arsenicals interaction with Zinc finger domain of the XPA (containing Zn 2+ ) at normal physiological condition, it has been found that only methylated metabolites; MMA III and DMA III (but not iAs III ) have stronger binding affinity to zinc finger proteins [119]. In fact, the studies that have shown binding of iAs III to zinc finger peptides were mostly performed using apo-Zn finger proteins [128, 131], thus, more studies are needed to evaluate that whether iAs III can also bind to Zn finger peptides or proteins (i.e., with Zn 2+ ) even under normal physiological conditions.…”
Section: Toxicities Of Arsenicmentioning
confidence: 99%
“…In particular, lung irritants in mice have been shown to trigger release of interleukin-6 by adipocytes, a cytokine that has been shown to increase metastasis of arsenic-exposed respiratory tissue. 67,68,76 Receptors of adiponectin, a cytokine produced by adipose tissue, are expressed in the lungs and play an anti-inflammatory role; however, as more fat tissue accumulates, secretion of adiponectin decreases. 77,78 Genetically modified mice unable to produce adiponectin had overall poor lung health, suggesting a link between healthy lung function and the adipocytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Here, subjects FEV 1 s or FVCs were entered in the multiple linear regression equation as the dependent variable and their ages, sex, and heights were entered as the independent variables. 68 Residuals were then calculated as the difference between the subjects observed FEV 1 or FVC and that predicted for them based on the linear regression equation and their age, sex, and height. Race had little impact on results and was not included.…”
Section: Methodsmentioning
confidence: 99%
“…46 In the bladder, cytokines can be inflamed by the metalloid, leading to potential malignancies. 47 Bladder cancer follows mechanisms of carcinogenesis similar to those of lung cancer. 48 Evidence suggests a synergistic relationship of the toxicant with tobacco.…”
Section: Properties Of Arsenic and Implications On Human Healthmentioning
confidence: 99%